Promosi Lagu “Takut” di Media Sosial Tiktok - Roro Aulia Arsyta Fajriyanti; Mariana Rista Ananda Siregar; Qoute Nuraini Cahyaningrum (UNIVERSITAS PAKUAN, 2024)
The purpose of this study is to understand how the marketing public relations of the song